1989
DOI: 10.1073/pnas.86.21.8314
|View full text |Cite
|
Sign up to set email alerts
|

Independent expression of human alpha or beta platelet-derived growth factor receptor cDNAs in a naive hematopoietic cell leads to functional coupling with mitogenic and chemotactic signaling pathways.

Abstract: Distinct genes encode a and f3 plateletderived growth factor (PDGF) receptors that differ in their abilities to be triggered by three dimeric forms of the PDGF molecule. We show that PDGF-receptor mitogenic function can be reconstituted in a naive hematopoietic cell line by introduction of expression vectors for either a or j3 PDGF receptor cDNAs. Thus, each receptor is independently capable of coupling with mitogenic signal-transduction pathways inherently present in these cells. Activation of either receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 36 publications
2
68
0
1
Order By: Relevance
“…While both PDGF a-and b-receptors are able to initiate DNA synthesis (Hosang et al, 1989;Matsui et al, 1989), it has been reported that the breceptor is a more potent mediator of mitogenicity compared to the a-receptor in certain cell types (Heidaran et al, 1993;Inui et al, 1994). Moreover, whereas the b-receptor mediates stimulation of chemotaxis, a-receptor inhibits chemotaxis, at least in certain cell types (Eriksson et al, 1992;Koyama et al, 1992;Siegbahn et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…While both PDGF a-and b-receptors are able to initiate DNA synthesis (Hosang et al, 1989;Matsui et al, 1989), it has been reported that the breceptor is a more potent mediator of mitogenicity compared to the a-receptor in certain cell types (Heidaran et al, 1993;Inui et al, 1994). Moreover, whereas the b-receptor mediates stimulation of chemotaxis, a-receptor inhibits chemotaxis, at least in certain cell types (Eriksson et al, 1992;Koyama et al, 1992;Siegbahn et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…PDGF is a multifunctional dimeric peptide occurring as either AA, BB homodimers or AB heterodimer isoforms. These dimeric configurations differentially activate the a or b subunits of the PDGF tyrosine kinase receptor and ligand binding studies have shown that the α-subunit binds either the A or B chain, and the β-subunit binds only the B chain [22,23]. These ligand/receptor combinations account for a wide range of PDGF-mediated effects in a range of cell types.…”
Section: Introductionmentioning
confidence: 99%
“…PDGF-BB was labeled by the method of Bolton and Hunter (specific activity, 2 x 104 cpm/ng) (2). 125I-PDGF-BB binding to cells was performed as previously described (28 For mitogenic assays, 32D transfectants were washed twice with phosphate-buffered saline (PBS) and plated at 3 x 105 cells per ml into Costar 24-well plates in RPMI 1640 medium containing 15% fetal calf serum with or without various concentration of PDGF-BB or murine IL-3 (Genzyme) as previously described (29). For the soft-agar assay, cells were plated At 10-fold serial dilutions in semisolid agarose medium containing RPMI 1640 medium supplemented with 15% fetal calf serum and 0.45% SeaPlaque agarose (FMC Corp.).…”
Section: Methodsmentioning
confidence: 99%
“…Colony formation was scored at 14 days. For determination of directed cell migration in response to PDGF-BB, modified Boyden chambers and Nuclepore filters (pore size, 5 ,um) were used as described previously (17,29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation